Carpal tunnel syndrome: mobilization and segmental stabilization - David Fedrigo Moraes; Andréa Licre Pessina Gasparini; Marco Aurélio Sertório Grecco; Nathalia Helen Neves Almeida; Tamiris Cassin Mainardi; Luciane Fernanda Rodrigues Martinho Fernandes
Abstract Introduction: Carpal tunnel syndrome is a compressive neuropathy, frequently seen in women. Conservative treatment for carpal tunnel syndrome focuses on control of symptoms and the nervous path, due to the possibility of double compression. Objective: To assess whether a protocol with emphasis on motor control techniques, including segmental cervical stabilization and neural mobilization, has better results in mechanical reorganization and reduction of symptoms when compared with classic therapeutic exercise techniques in the conservative treatment of carpal tunnel syndrome. Methods: This pilot study was a randomized, double-blind clinical trial, involving 11 women with an average age of 54 (± 6) years, allocated to either a classical kinesiotherapy group (CG) or experimental group (EG). The intervention spanned 12 weeks, with assessments prior to and following therapy, using the monofilament test, handgrip dynamometer, and BCTQ, DASH, and PRWE questionnaires. All normally distributed data was analysed with Student's T-tests. Results: Both groups exhibited an increase in grip strength and relief of symptoms with improved functionality. There was a significant reduction in sensitivity noted in the CG group, and a significant increase in grip strength observed in the EG group. Conclusion: The experimental protocol group exhibited better results in mechanical reorganization, reflected in increased strength, sensitivity, and improved functionality, when compared to the group with conventional therapeutic exercise, but without the same symptomatic reduction.